Translational bioinformatics applications in healthcare - Raza, Khalid; Dey, Nilanjan, 1984- (Boca Raton, FL : CRC Press, 2021)
"Translational bioinformatics (TBI) involves development of storage, analytics and advanced computational methods to harvest knowledge from voluminous biomedical and genomic data into 4P healthcare (proactive, predictive, preventive and participatory). This book offers a detailed overview and concepts of TBI, biological and clinical databases, clinical informatics, and pertinent real-case applications. It further illustrates recent advancements, tools, techniques, and applications of TBI in healthcare including IoT potential, toxin databases, medical image analysis and telemedicine applications, analytics of COVID-19 CT-images, viroinformatics and viral diseases, COVID-19 related research"--
OCLC-licensed vendor bibliographic record.
Keywords: Bioinformatics; Drug development; Medical informatics; SCIENCE / Biotechnology; COMPUTERS / Computer Engineering